Experimental assessment of microwave ablation computational modeling with MR thermometry. Issue 9 (16th July 2020) - Faridi, Pegah; Keselman, Paul; Fallahi, Hojjatollah; Prakash, Punit
Abstract : Purpose: Computational models are widely used during the design and characterization of microwave ablation (MWA) devices, and have been proposed for pretreatment planning. Our objective was to assess three‐dimensional (3D) transient temperature and ablation profiles predicted by MWA computational models with temperature profiles measured experimentally using magnetic resonance (MR) thermometry in ex vivo bovine liver. Materials and methods: We performed MWA in ex vivo tissue under MR guidance using a custom, 2.45 GHz water‐cooled applicator. MR thermometry data were acquired for 2 min prior to heating, during 5–10 min microwave exposures, and for 3 min following heating. Fiber‐optic temperature sensors were used to validate the accuracy of MR temperature measurements. A total of 13 ablation experiments were conducted using 30–50 W applied power at the applicator input. MWA computational models were implemented using the finite element method, and incorporated temperature‐dependent changes in tissue physical properties. Model‐predicted ablation zone extents were compared against MRI‐derived Arrhenius thermal damage maps using the Dice similarity coefficient (DSC). Results: Prior to heating, the observed standard deviation of MR temperature data was in the range of 0.3–0.7°C. Mean absolute error between MR temperature measurements and fiber‐optic temperature probes during heating was in the range of 0.5–2.8°C. The mean DSC between model‐predicted ablation zones and MRI‐derived Arrhenius thermal damage maps for 13 experimental set‐ups was 0.95. When comparing simulated and experimentally (i.e. using MRI) measured temperatures, the mean absolute error (MAE %) relative to maximum temperature change was in the range 5%–8.5%. Conclusion: We developed a system for characterizing 3D transient temperature and ablation profiles with MR thermometry during MWA in ex vivo liver tissue, and applied the system for experimental validation of MWA computational models.